2021
DOI: 10.3389/fenvs.2021.682669
|View full text |Cite
|
Sign up to set email alerts
|

The STEM Enhancement in Earth Science “Mosquito Mappers” Virtual Internship: Outcomes of Place-Based Engagement with Citizen Science

Abstract: In this paper, we describe a virtual high school earth science enhancement program that embeds a citizen science experience within a scientist-mentored research internship. We demonstrate the success of the program as measured by knowledge of pertinent science concepts and processes, and changes in future career orientation, and explore the role of place-based citizen science in interns’ experience of their research projects. The STEM Enhancement in Earth Science (SEES) Mosquito Mappers Virtual Internship conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our results align with and support previous research that shows that learning can be more meaningful when students engage in place-based and project-based science that allow them to apply scientific concepts in a real-world setting (e.g. (Manzanal et al, 1999;Flanagan et al, 2019;Cho et al, 2021). Such experiences, especially in the context of environmental science education, can be transformative for students and may result in longer-term outcomes for environmental conservation and restoration (Ballard et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Our results align with and support previous research that shows that learning can be more meaningful when students engage in place-based and project-based science that allow them to apply scientific concepts in a real-world setting (e.g. (Manzanal et al, 1999;Flanagan et al, 2019;Cho et al, 2021). Such experiences, especially in the context of environmental science education, can be transformative for students and may result in longer-term outcomes for environmental conservation and restoration (Ballard et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…[ 43 ]; Cho et al. [ 111 ]; Christoffel [ 45 ]; Conrad and Hilchey [ 112 ]; Cronje et al. [ 46 ]; da Silva and Heaton [ 113 ]; Dickinson et al.…”
Section: Resultsmentioning
confidence: 99%
“…[109]; Aivelo and Huovelin[34]; Ballard et al[38]; Ballard et al[39]; Bedessem et al[110]; Carson et al[43]; Cho et al[111]; Christoffel[45]; Conrad and Hilchey[112];Cronje et al[46]; da Silva and Heaton[113];Dickinson et al [114]; English et al [52]; Grossberndt et al [115]; Haywood et al [57]; Hiller and Kitsantas [116]; Hoekstra et al [117]; Isley et al [62]; Johnson et al [63]; Kloetzer et al [69]; Lewis and Carson [118]; Luesse et al [74]; Mady et al [76]; Merenlender et al [80]; Peter et al [85]; Phillips et al [87]; Price and Lee [119]; Ross-Hellauer et al [120]; Trumbull et al [121]; Walker et al [102]; Walker et al [27]; Zarybnicka et al [104] Jordan et al [64] none 33 change in interest in studying science or pursuing career in science Ballard et al [39]; Cho et al [111]; Hiller and Kitsantas [58]; Johnson et al [63]; Koomen et al [122]; Luesse et al [74]; Mahajan et al [123]; Rosas et al [124]; Seifert et al [95]; Vitone et al [108]; Wallace and Bodzin [125] [37]; Ballard et al [39]; Costa et al [127]; Frigerio et al [128]; Johnson et al [63]; Mahajan et al [129]; Schaefer et al [90]; Shinbrot et al [107]; Stepenuck and Green [98]; Walker et al [27]…”
mentioning
confidence: 99%
“…An evaluation of the internship outcomes by Cho et al demonstrated that citizen science tools and data could underpin a robust, cost-effective student research experience offered in a distributed virtual setting [ 107 ]. Mosquito Habitat Mapper, originally developed to support NASA educational objectives, lowers barriers to science participation online and broadens access to science, technology, engineering, and math enhancement opportunities.…”
Section: Discussionmentioning
confidence: 99%